Quasielastic Light Scattering and Structure of Nanodroplets Mixed with Polycaprolactone. (23rd June 2014) - Sharifi, Soheil
Abstract : The interaction of polycaprolactone (PCL) with droplets of a microemulsion is studied with quasielastic light scattering and small angle X-ray scattering At constant droplet size we vary the PCL concentration and there is clear evidence for an increasing attractive interaction of the droplets from structural investigations with small-angle X-ray scattering (SAXS). The collective diffusion coefficient (D c ) of the droplets is monitored with quasielastic light scattering (QELS). We mainly focus on the variation of the dynamic behavior as a function of the PCL concentration and length scale (M.W. = 5000 and 10000) in microemulsion. With increasing PCL concentration and length scale the dynamics of the system slow down. A hard sphere model with depletion potential can fit well the SAXS experiment of microemulsion mixed with PCL. The results show with increase of PCL on microemulsion the size of droplets is constant at 83Å but the size ratio of polymer to droplets is changing.